Fuzzy Data Envelopment Analysis And Its Applications For Aggregating Preference Ranking - Langroudi, Madjid Zerafat Angiz E (2010)

(untitled)
Over the past two decades, Data Envelopment Analysis (DEA) has appeared as an important tool in the field of efficiency measurement. DEA is used to compare Decision Making Units (DMUs) such as bank branches, hospitals, sales outlets, which consume one or more non-homogenous inputs to produce one or more nonhomogenous outputs. The DMUs consume the same inputs and produce the same outputs but generally at varying levels. One of the main characteristics of DEA is its sensitivity to data. That is, inaccurate data may divert effectively the results of efficiency analysis from its actual value. But accurate measurement in many real world problems, due to either non-availability of sophisticated measurement tools or qualitative nature of the phenomena may not be possible. This kind of information can be represented as fuzzy numbers or linguistic terms.